The function‐dominance correlation drives the direction and strength of biodiversity–ecosystem functioning relationships. (22nd June 2021) - Crawford, Michael S.; Barry, Kathryn E.; Clark, Adam T.; Farrior, Caroline E.; Hines, Jes; Ladouceur, Emma; Lichstein, Jeremy W.; Maréchaux, Isabelle; May, Felix; Mori, Akira S.; Reineking, Björn; Turnbull, Lindsay A.; et al.
Abstract: Community composition is a primary determinant of how biodiversity change influences ecosystem functioning and, therefore, the relationship between biodiversity and ecosystem functioning (BEF). We examine the consequences of community composition across six structurally realistic plant community models. We find that a positive correlation between species' functioning in monoculture versus their dominance in mixture with regard to a specific function (the "function‐dominance correlation") generates a positive relationship between realised diversity and ecosystem functioning across species richness treatments. However, because realised diversity declines when few species dominate, a positive function‐dominance correlation generates a negative relationship between realised diversity and ecosystem functioning within species richness treatments. Removing seed inflow strengthens the link between the function–dominance correlation and BEF relationships across species richness treatments but weakens it within them. These results suggest that changes in species' identities in a local species pool may more strongly affect ecosystem functioning than changes in species richness. Abstract : We examine the consequences of community composition on the structure of biodiversity and ecosystem functioning (BEF) relationships across six structurally‐realistic plant community models. We find that the correlation between species' functioning in monoculture vs. their dominance in mixture with regards to a specific function (A, B; the "function‐dominance correlation") generates contrasting BEF patterns across and within species richness treatments (C). These results, supported by empirical BEF results, suggest that changes in species' identities in a local species pool may more strongly affect ecosystem functioning than changes in species richness.